Atypical Teratoid/Rhabdoid Tumor in a Young Adult: A Case Report and Literature Review - Zarei, Elham; Anvari, Kazem; Arastouei, Soudeh; Jafarian, Amir Hossein (Reports of Radiotherapy and Oncology, 2022)
Atypical teratoid/rhabdoid tumor (AT/RT) is a very rare tumor, mostly found in the posterior fossa of children aged under three years. Combined modality treatment appears to improve the results. Herein, this report aimed to present a case of intramedullary intradural AT/RT of the anterior thecal sac in a 17-year-old girl with subtotal resection by undergoing adjuvant radiotherapy and sequential chemotherapy.